Detection of KRAS mutation via ligation-initiated LAMP reaction - Fu, Yixin (Sci Rep, 2019)
KRAS mutations are abnormalities widely found in genomic DNA and circulating tumor DNA (ctDNA) of various types of cancers. Thus, highly sensitive detection of KRAS mutations in genomic DNA is of great significance in disease diagnosis and personalized medicine. Here, we developed a ligation-initiated loop-mediated isothermal amplification (LAMP) assaying method for ultrasensitive detection of KRAS mutation. In the presence of mutant KRAS DNA (mutDNA), the dumbbell-shaped structure (DSS) is formed by the specific ligation of two substrates (SLS1 and SLS2), which act as a template to initiate the following LAMP amplification. Making use of the outstanding specificity of ligation reaction and superior amplification of LAMP, 10 aM mutDNA can be accurately determined. In addition, as low as 0.1% mutDNA can be detected in the presence of a large excess of wild-type KRAS DNA (wtDNA), indicating the high sensitivity and specificity of the method. Furthermore, this strategy has been successfully applied for detection of a KRAS mutation from tissue samples of colorectal cancer patients. Thus, the developed ligation-initiated LAMP fluorescence assaying strategy presents a promising prospect for ultrasensitive detection of mutations.